PENGARUH NILAI-NILAI KRISTIANI PENDIDIKAN SEKOLAH KATOLIK DAN NILAI-NILAI BUDAYA JAWA TERHADAP PERILAKU AGRESIF REMAJA - Martinus Sariya Giri (P3TK, Sanata Dharma University, 2013)
The future of a nation and a church is on the shoulder of its youth. Education bears a significant role in guiding and empowering the youth. Education provides means as well as medium for character and values building. Amidst an aggressive society, how can a Catholic school offer an education to counter particularly through an internalization of Christian values? How can their students learn and internalize those values.This research is aimed at revealing and measuring the teenagers understanding of Christian values as taught in a Catholic school and also on the role of Javanese cultural values in life of the teenagers with aggressive behavior. This research is an attempt to explain phenomena of the increasing aggressive behavior among teenagers in mass media despite the existing educational accompaniment. Second Vatican Council emphasized the importance of education in the Church as a medium for human development and character development (GE 1). In the same article, it is stated that children and young people posses primary rights to be supported and enable them to appreciate a sincere conscience as well as moral values so as to understand and to love God in a more perfect way. The Council also accentuated specifically that education is duty of the Church, as a medium to spread the Good News towards fellow people (GE 3).Result of the research concludes that understanding of Christian and cultural values help significantly to reduce teenagers aggressive behavior. On the other hand, what should not be undermined is the influence television, the internet as well as the changing role of parents.Based on findings of this research, the writer should deepen the vision and mission of a Catholic education by his theological and pastoral reflection particularly by reviewing the history of educational ministry of FIC Congregation which has been established since 1840. The writer concludes that educational ministry should remain as primary mission of the evangelizing Church.